An Empirical Window on Rational Expectations Formation - Pollock, Richard L.; Suyderhoud, Jack P. (The Review of Economics and Statistics, 1992)
Persons' expectations regarding their ultimate life span provide a tractable empirical opportunity to test for rational expectations. To the extent people only utilize information from "current life tables, " they underestimate the more relevant ultimate life expectancy that results from on-going improvements in mortality experience not reflected in these tables. The expectations observed in the authors' empirical work are not consistent with rational-expectations models. All available information about life expectancies and their trends were not used by the surveyed households in forming life-span expectations. This deficiency precludes correct estimation of the ultimate life expectancy necessary for informed life-cycle choices. Copyright 1992 by MIT Press.